Association between morphometric measurements and disease progression in Cavalier King Charles Spaniels with preclinical degenerative mitral valve disease: A retrospective longitudinal study - Sara Ghilardi; Fabio Maria Colombo; Mara Bagardi; Michele Polli; Maria Cristina Silvia Cozzi; Paola Giuseppina Brambilla (PLoS ONE, 2026)
Cavalier King Charles Spaniels (CKCS) are predisposed to a hereditable form of myxomatous mitral valve disease (MMVD) with a high incidence and a high risk of disease progression. Gender is recognized as a risk factor for the development of the disease in the breed. However, patient’s morphological traits associated with disease progression have not been identified. The aim of this study was to analyze the association between preclinical MMVD progression and morphometric features in CKCSs. This was a retrospective, time-to-event, longitudinal study. Medical records of 302 CKCSs were reviewed from April 2019 to January 2023. The final sample size counted 52 adult (≥ 1 year) MMVD-affected CKCSs classified as American College of Veterinary Internal Medicine (ACVIM) stage B1, with a minimum 24-month follow-up period and ≥ 2 follow-up examinations. At baseline examination, each dog underwent echocardiography and morphometric evaluation of the body, the head and the thorax; dogs were re-examined at 6- or 12-month intervals, and progression to ACVIM stage B2 was registered as the primary outcome. The median follow-up time was 1270.50 days (interquartile range (IQR, 25 th and 75 th ): 994.75–1525.50 days). In the time-to-event analysis, 17 (32.7%) dogs reached the endpoint, with a median time of 1548 days. Results from the Cox multiple regression analysis with inverse probability weighting (IPW) analysis showed that the following morphometric variables had an association ( p < 0.05) with MMVD progression: thoracic length (hazard ratio (HR): 1.97, p = 0.002), thoracic circumference (HR: 0.61, p = 0.03), and thoracic index (HR: 0.86, p = 0.049). Data obtained from this study suggest that an association between mitral valve disease progression and thoracic morphology exists in MMVD-affected CKCSs classified as ACVIM stage B1. Morphological features should be considered along with other known risk factors for the breed when assessing the risk of MMVD progression in CKCSs.